Comparison of Learning Evaluation Systems in The 2013 Curriculum and Independent Curriculum at Bengbulang 2 Elementary School - Alwi Sofyan; M. Ilham Rahman Riyadi (Universitas Sebelas Maret, 2022)
This study aims to compare the learning evaluation system in the 2013 curriculum and the Merdeka curriculum at SD Begbulang 2. The method used is a comparative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects were teachers and students of grades V and VI. The results of the study show that the learning evaluation system in the Merdeka curriculum at SD Begbulang 2 focuses more on developing students’ skills and character, while the evaluation system in the 2013 curriculum places more emphasis on achieving academic grades. However, it should be recognized that both evaluation systems have their advantages and disadvantages. Therefore, it is necessary to improve and perfect the learning evaluation system in the two curricula.